Dancing around the Cauldron with Rangda, the Balinese widow-witch: Exploring gender relations and attitudes toward women and children in Southeast Asia - Kathleen Nadeau (Masyarakat, Kebudayaan dan Politik, 2020)
By taking a cross-cultural approach based on library research, content analysis, and fieldwork in the Philippines, this paper compares Southeast Asian and European tales. The Southeast Asian tales are rooted in local philosophical and cultural traditions. Balinese literature is replete with descriptions of rituals to ward off vampires. The flying half-bodied Aswangs in the Philippines, like their Malaysian sisterlings, can be shown to bear some resemblance to Balinese witches who culminate in the Rangda, the queen of witches. The Balinese ritual battle between the troubled widow witch Rangda and the gentle Barong offers a circular view of history that arguably holds to a universal notion of good and evil. In contrast, European witch tales can be traced back to the hysterical witch hunts and persecution of female midwives and healers in Medieval times that were perceived as threatening the power and authority of male doctors, priests, and landed government officials. The conclusion is that Southeast Asian lore connotes a different set of gender relations and attitudes toward women and children than European origin.